Examining psychological distress in orphan children - Jaffer, Usman; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Ahmad H.Osman, Rahmah; Mohd Zaki, Muhammad Zul Hairri Amir; Azeman, Haziq Iqbal; Mohd Muzamir, Nurul Sharfina; Md Reshad, Husna Zahirah; Aminondin, Sofea 'Aisyah (Global Academic Excellence (M) Sdn Bhd, 2023)
The prevalence of depression, anxiety, and stress among orphaned children is a critical concern requiring careful examination. Orphaned children grapple with unique challenges, such as the loss of parental support and the disruption of stable familial connections, with significant implications for their mental well-being and overall psychological health. This study investigates the prevalence of depression, anxiety, and stress among orphaned children, with a specific focus on gender-related variations. A total of 26 orphans, aged 7 to 12 years, were recruited from Pusat Jagaan Hembusan Kasih Sayang in Kuantan, Pahang. The Depression, Anxiety, and Stress Scale (DASS-21) was employed for assessment. While no significant values for DASS Test variables were detected, there were gender-related differences in the psychological well-being of the children in the orphanage. The prevalence of depression, anxiety, and stress among orphans from Pusat Jagaan Hembusan Kasih Sayang is low. Notably, females exhibit higher levels of depression, anxiety, and stress compared to males.